Relationship of serum beta-synuclein with blood biomarkers and brain atrophy - Oeckl, Patrick; Anderl-Straub, Sarah; Danek, Adrian; Diehl-Schmid, Janine; Fassbender, Klaus; Fliessbach, Klaus; Halbgebauer, Steffen; Huppertz, Hans Jürgen; Jahn, Holger; Kassubek, Jan; Kornhuber, Johannes; Landwehrmeyer, Bernhard; et al. (Alzheimers & Dementia, 2022)
Background: Recent data support beta-synuclein as a blood biomarker to study synaptic degeneration in Alzheimer's disease (AD). Methods: We provide a detailed comparison of serum beta-synuclein immunoprecipitation – mass spectrometry (IP-MS) with the established blood markers phosphorylated tau 181 (p-tau181) (Simoa) and neurofilament light (NfL) (Ella) in the German FTLD consortium cohort (n = 374) and its relation to brain atrophy (magnetic resonance imaging) and cognitive scores. Results: Serum beta-synuclein was increased in AD but not in frontotemporal lobar degeneration (FTLD) syndromes. Beta-synuclein correlated with atrophy in temporal brain structures and was associated with cognitive impairment. Serum p-tau181 showed the most specific changes in AD but the lowest correlation with structural alterations. NfL was elevated in all diseases and correlated with frontal and temporal brain atrophy. Discussion: Serum beta-synuclein changes differ from those of NfL and p-tau181 and are strongly related to AD, most likely reflecting temporal synaptic degeneration. Beta-synuclein can complement the existing panel of blood markers, thereby providing information on synaptic alterations. Highlights: Blood beta-synuclein is increased in Alzheimer's disease (AD) but not in frontotemporal lobar degeneration (FTLD) syndromes. Blood beta-synuclein correlates with temporal brain atrophy in AD. Blood beta-synuclein correlates with cognitive impairment in AD. The pattern of blood beta-synuclein changes in the investigated diseases is different to phosphorylated tau 181 (p-tau181) and neurofilament light (NfL).
CRIS-Team Scopus Importer:2022-10-07
Keywords: Alzheimer's disease; beta-synuclein; blood biomarker; brain atrophy; dementia; frontotemporal lobar degeneration; FTLD; NfL; p-tau181; synaptic degeneration